2022
DOI: 10.1097/pas.0000000000001943
|View full text |Cite
|
Sign up to set email alerts
|

Morphologic and Molecular Heterogeneity of Cervical Neuroendocrine Neoplasia

Abstract: Neuroendocrine neoplasms (NENs) of the cervix are rare aggressive tumors associated with poor prognosis and only limited treatment options. Although there is some literature on molecular underpinnings of cervical small cell neuroendocrine carcinomas (SCNECs), detailed morphologic and associated molecular characteristics of cervical NENs remains to be elucidated. Herein, 14 NENs (SCNEC: 6, large cell neuroendocrine carcinoma [LCNEC]: 6, neuroendocrine tumor [NET]: 2), including 5 admixed with human papillomavir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 86 publications
0
6
0
Order By: Relevance
“…RB1 mutations were not consistent in all the studies. Only one study showed a 66.7% RB1 alteration in SCCC; others varied from 0% to 10% [13,17,18,20,21,28–30,58]. RB1 alterations decreased overall survival in a recent study [59].…”
Section: Discussionmentioning
confidence: 99%
“…RB1 mutations were not consistent in all the studies. Only one study showed a 66.7% RB1 alteration in SCCC; others varied from 0% to 10% [13,17,18,20,21,28–30,58]. RB1 alterations decreased overall survival in a recent study [59].…”
Section: Discussionmentioning
confidence: 99%
“…Cervical small cell neuroendocrine carcinoma has similar HPV infection status [16] and gene mutations [17][18][19] compared to more common cervical epithelial tumors but it has a higher proportion of lymph node metastasis, poorer treatment response, and survival prognosis. A large population-based analysis from NCDB revealed patients with cervical neuroendocrine carcinoma were younger and more often diagnosed with metastatic disease at presentation compared to patients with squamous cancer.…”
Section: Discussionmentioning
confidence: 99%
“…The molecular profile of uterine cervix MiNEN is also poorly studied; to the best of our knowledge, there are no systematic studies on larger number of patients and only few reported cases in small series are available [ 6 , 8 , 12 , 15 , 16 ]. Our molecular analysis found that the adenocarcinomatous component of the neoplasm carried GNAS mutation,in fact GNAS mutations have been reported in numerous tumors of the gastrointestinal tract and also in endocervical mucinous adenocarcinoma [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…In 2020 Eskander and colleagues [ 7 ] studied a large cohort of patients with high-grade cervical neuroendocrine carcinomas; they found that the most frequent altered genes were PIK3CA , MYC, TP53 , and PTEN and that the main interested pathways were PIK3CA/AKT/mTOR and RAS/MEK . In a recent work, Ordulu and colleagues found a similar set of mutations in a series of 14 NEN of the cervix, also including RB1 and MSH6 genes mutations [ 16 ]. However, ERBB2 mutations involving cervical neuroendocrine carcinomas are rarely reported in literature [ 5 , 21 ].…”
Section: Discussionmentioning
confidence: 99%